2016
DOI: 10.3923/rjet.2016.75.81
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Human Health Risk for Heavy Metals in Imported Rice and its Daily Intake in Iran

Abstract: This study investigated the amount of Pb, Cd, Cr, Ni, Zn and Cu in samples of imported Indian rice (Oryza sativa) available in Iranian markets. Twenty brands of Indian rice which widely-consumed were collected from Iranian local markets. Five samples of each brand were collected and analyzed. After the rice grains were digested through acid digestion method, Pb, Cd, Cr, Ni, Zn, Cu values of each brand were determined by atomic absorption spectrometer. The results showed that cadmium content could not be detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…El arroz posee un alto valor nutricional, pero, es importante destacar la presencia de contaminantes, especialmente los metales tóxicos, como por ejemplo, arsénico (As), plomo (Pb) y cadmio (Cd). Debido al alto consumo de arroz, los consumidores están expuestos a altos niveles, por lo que, se deberían tomar medidas adecuadas para evitar su incremento [8][9][10][11]. La exposición prolongada al arsénico a través del consumo de agua y alimentos contaminados puede causar cáncer y lesiones cutáneas.…”
Section: Introductionunclassified
“…El arroz posee un alto valor nutricional, pero, es importante destacar la presencia de contaminantes, especialmente los metales tóxicos, como por ejemplo, arsénico (As), plomo (Pb) y cadmio (Cd). Debido al alto consumo de arroz, los consumidores están expuestos a altos niveles, por lo que, se deberían tomar medidas adecuadas para evitar su incremento [8][9][10][11]. La exposición prolongada al arsénico a través del consumo de agua y alimentos contaminados puede causar cáncer y lesiones cutáneas.…”
Section: Introductionunclassified
“…Other studies reported higher levels of exposure than our revealed levels for Lebanon and the UAE. Two Iranian studies published such high levels;Rabbani et al (2015) stated that exposure was 0.0035 and 0.004 mg/kg/day from Iranian and non-Iranian rice, respectively, andMahvi et al (2016) reported exposure from Indian rice Iran equivalent to 0.88 mg/kg bw/week. Likewise, higher levels were stated byJahiruddin et al in Bangladesh (2017) (74.1±43.5 μg/day) andOrisakwe et al (2012) in Nigeria (0.…”
mentioning
confidence: 99%